Cheating: It depends how you define it - Kennette, Lynne N.; Jelenic, Milan (Canadian Perspectives on Academic Integrity, 2023)
Cheating in academia is defined multidimensionally and might include dishonesty, fraud, stealing, and unauthorized use. This behaviour appears to be on the rise in higher education, though it may be somewhat subjective. Beyond the ethical issue of cheating, inadequately learned skills and unqualified practitioners put lives at risk (e.g., medicine, engineering), as well as the institution’s reputation and integrity in producing proficient graduates. We asked Canadian students and faculty from a two-year college to define academic cheating in their own words and rate a number of behaviours to indicate their perception of whether the behaviour should be considered cheating or not. Overall, there was a great overlap between the themes evoked in students’ and faculty’s definitions of cheating. Differences between students’ and faculty’s ages might suggest a different degree of moral reasoning which may have impacted the responses. This study further contributes to knowledge about cheating because we surveyed college students (rather than university students), which are greatly under-represented in the literature.